2020
DOI: 10.1016/j.precamres.2020.105610
|View full text |Cite
|
Sign up to set email alerts
|

Episodic magmatism during the growth of a Neoproterozoic oceanic arc (Anti-Atlas, Morocco)

Abstract: We present an integrated study combining detailed field, geochronological and geochemical data of a Neoproterozoic intra-oceanic arc systems exposed in the Pan-African belt of the Moroccan Anti-Atlas. The arc rock units exposed in Bou Azzer and Sirwa inliers consist of a tectonic patchwork of back-arc ophiolitic sequences to the north thrusted onto accreted arc complexes to the south. Arc complexes are composed of amphibolite, granodioritic and granitic gneisses intruded by various undeformed hydrous ultramafi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(21 citation statements)
references
References 94 publications
2
18
0
1
Order By: Relevance
“…This ophiolitic sequence is extensively tectonized, marked by tectonic contacts between most of its ophiolitic terms (see Fig. 2 in Triantafyllou et al, 2020). Three major tectonic slices were recognized in the studied area, whose sole appears systematically represented by soft serpentinite bands.…”
Section: Introductionmentioning
confidence: 85%
See 3 more Smart Citations
“…This ophiolitic sequence is extensively tectonized, marked by tectonic contacts between most of its ophiolitic terms (see Fig. 2 in Triantafyllou et al, 2020). Three major tectonic slices were recognized in the studied area, whose sole appears systematically represented by soft serpentinite bands.…”
Section: Introductionmentioning
confidence: 85%
“…These reactions induced by contact metamorphism are responsible for the formation of garnet-bearing leucosomes during incipient partial melting of hornblende-rich rocks. As well as for the Iriri-Tachakoucht-Tourtit arc complex of the Sirwa inlier, the geochemical and isotopic studies of D' Lemos et al (2006) on the Tazigzaout complex and of Triantafyllou et al (2018Triantafyllou et al ( , 2020 on the Bougmane complex have shown that all these rocks are the product of a polyphased magmatic activity from a magmatic arc system located in an intra-oceanic domain.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…La genèse des gisements de plomb géants au Protérozoïque a été mise en relation avec l'intense mobilisation crustale lors de la formation du continent Nuna, la stabilisation de la lithosphère et l'ouverture de grands bassins au début du Mésoprotérozoïque (Sawkins, 1989 ;Hawkesworth et al, 2020). La construction continentale sur la marge nord du craton ouest-africain démarre un milliard d'années plus tard avec la formation du Gondwana, un continent à forte épaisseur crustale et largement émergent au-dessus du niveau de la mer (Traintafyllou et al, 2020). Le stock de plomb des formations volcaniques panafricaines devient alors plus facilement accessible et sera essentiel au Maroc.…”
Section: Discussionunclassified